Association between endometrial indoleamine 2,3-dioxygenase expression level and pregnancy outcomes in women undergoing first in vitro fertilization treatment - Su Liu; Ling Hong; Yuye Li; Ruochun Lian; Xiaohui Wang; Yong Zeng (BMC, 2021)
Abstract Background Indoleamine 2,3-dioxygenase (IDO) has been reported to play a key role in placental development during normal pregnancy. However, the question of whether endometrial IDO expression affects in vitro fertilization (IVF) pregnancy outcomes remains unclear. The current study was undertaken to investigate whether there was any association between endometrial IDO immunohistochemical staining and IVF treatment outcome. Methods This retrospective study was designed to compare pregnancy outcomes among women with different endometrial IDO expression levels under their first IVF treatment. A total of 140 women undergoing their IVF treatment were selected from January 2017 to December 2017. Endometrial samples were collected during mid-luteal phase before IVF cycle. The endometrial IDO expression levels were analyzed by immunohistochemistry, and compared between women who were pregnant or not. A logistic regression analysis was performed to determine the impact of endometrial IDO staining on live birth. Results No significant differences in the endometrial IDO immunohistochemical staining were found between women who had clinical pregnancy and those who failed (P>0.05). However, the endometrial IDO staining was significantly higher among women who had live birth compared with those who had no live birth (P=0.031). Additionally, after adjusting for differences in maternal age, BMI and duration of gonadotropin stimulation, women with higher IDO expression level had an increased live birth rate (adjusted odds ratio [aOR] 2.863, 95% confidence interval [CI] 1.180-6.947). Conclusions Higher endometrial IDO expression level during mid-luteal phase is associated with an increased live birth rate in women undergoing their first IVF treatment.